“A Virgine and a Martyr both”: The Turn to Hagiography in Heywood’s Reformation History Play - Di Salvo, Gina (Renaissance and Reformation / Renaissance et Réforme)

(untitled) (Iter Press, 2018)
This article considers the narrative and theatrical strategies used by Thomas Heywood to sanctify Elizabeth I as a virgin martyr saint in the remarkable, yet understudied, Reformation history play If You Know Not Me, You Know Nobody, Part I, or the Troubles of Queen Elizabeth (ca. 1605). I examine how Heywood reads against Foxe even as he draws on the history of the English Reformation from the Book of Martyrs to create a narrative of virgin martyrdom; I discuss how the play’s miraculous theatricality re-forms past iterations of religious knowledge in drama, and show that the play recovers hagiography for English Protestantism. I conclude by suggesting that Heywood invented the Stuart saint play.